Potential plant–aphid–fungal associations aiding conservation biological control of cereal aphids in Argentina - Manfrino, Romina Guadalupe (2013)
The overall aim of this study was to identify potential associations between aphids and plants as reservoirs of entomophthoralean fungi. A survey of weeds associated with wheat field borders in two different localities was performed over two years, from April 2010 to April 2012 in the Pampeana central region, Argentina. On each sampling date, five individuals of each plant species were randomly selected, and healthy and infected aphids were collected and quantified once a month. The taxonomic identities of both aphid hosts and entomophthoralean fungi were established. Aphid?fungus associations identified as favorable for inclusion in conservation biological control strategies in borders of wheat crops are the following: Sonchus oleraceus (L.)/Hyperomyzus carduellinus (Theobald), Uroleucon sonchi (L.)/Pandora neoaphidis (Remaudiere & Hennebert) Humber; S. oleraceus (L.)/H. carduellinus (Theobald)/Zoophthora radicans (Brefeld) Batko; Lamium amplexicaule (L.)/Cryptomyzus korschelti B^orner/P. neoaphidis, Z. radicans, Entomophthora planchoniana Cornu; Foeniculum vulgare (Miller)/Dysaphis apiifolia (Theobald)/Z. radicans; Morrenia brachystephana Griseb/Aphis nerii Boyer de Fonscolombe/P. neoaphidis and Brassica rapa L./Brevicoryne brassicae (L.)/P. neoaphidis.